Design and Prototype of SIMAKLIK: Web-based Information System to Support Document Management and Self-Assessment of Primary Care Clinics Accreditation - Anun Fatikah; Dian Budi Santoso (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
The preparation of primary care clinic accreditation in Indonesia still uses a manual system, causing unpreparedness and slowing down the performance of officers in preparing for accreditation. Other inhibiting factors are workload and adjustments to the latest accreditation standards. Accreditation is an important point in maintaining the quality of health care facilities. The fact that clinic accreditation in Indonesia is still quite low, only 1.7% of private clinics have been accredited out of 10,380. Driven by technological developments, it is necessary to develop a system that helps facilitate the documentation management and self-assessment. The research aims to design a system from problem analysis, system architecture to functionality. This research method using design thinking involves potential users at the Permata Keluarga Clinic and the design refers to the Clinic accreditation standards by the Ministry of Indonesian through H.K.01.07/MENKES/1983/2022. SIMAKLIK can be used by leaders and quality team members, accreditation assistance officers and surveyors. Features of this system prototype include: systematic documentation in accordance with the accreditation standard, self-assessment report features, dashboard, notes and recommendations features. This prototype has been successfully tested to users with SUS Score results of 81.78. The SUS Score results are categorized as grade B or very good, which indicates that the system's acceptability and usability are good. SIMAKLIK has contributed to the development of a document management system as an innovative product in health care facilities, especially clinics. In the future, that prototype can be followed up through development by the engineer team.